NASAL OBSTRUCTION AND EUSTACHIAN TUBE DYSFUNCTION: HOW ARE THEY RELATED? - Parvez Kamal, Nudrat; Harkare, Vivek (International Journal of Clinical and Biomedical Research, 2015)
Eustachian tube is an osseocartilagenous tube which connects middle ear with nasopharynx. It has been suggested that any pathology affecting the nose, paranasal sinuses or nasopharynx may lead to Eustachian tube dysfunction and middle ear hypoventilation. Hence, we decided to take up a study to assess the effect of nasal obstructive lesions on Eustachian tube function by Impedance Audiometry and to see if it improves or not after corrective surgery. The present study was conducted prospectively in 44 patients with a male: female ratio of 2.14:1 and age ranging from 18 to 68 years, having abnormal tympanograms (type B/C) in atleast one ear who underwent nasal surgery for nasal obstructive lesions. The study favours the observation that surgery for nasal obstruction significantly improves tubal function and middle ear ventilation by 4 weeks postoperatively. Nasal obstructive lesions lead to Eustachian tube dysfunction by causing airflow turbulence in the post nasal space as a result of asymmetrical airflow in the two nasal passages. Hence, corrective surgery for nasal obstruction should be considered atleast 4 weeks before undertaking the middle ear surgery to improve middle ear ventilation, thereby improving the success rates of middle ear surgery. KEYWORDS: Eustachian tube; Paranasal sinuses; Osseocartilagenous; Nasopharynx.